THE PRINCIPLE OF THE BEST INTERESTS OF THE CHILD IN LAW ENFORCEMENT AGAINST CHILDREN WHO COMMIT RAPE - Cindy Shafira; Prija Djatmika; Nurini Aprilianda (CV. RADJA PUBLIKA, 2025)
Handling rape cases involving children as perpetrators has become a complicated issue within the juvenile justice system in Indonesia. This crime not only causes deep psychological wounds to the victims, who are also still children, but also presents complex legal issues in the law enforcement process against the perpetrators who are legally minors. The principle of